Determination Du Niveau De Fibres Dans L’aliment Granule Chez L’aulacodine (Thryonomys Swinderianus, Temminck 1827): Impacts Sur Les Performances Zootechniques - Bedel, Alla Konan Jean; Magloire, Yapi Yapo; Moussa, Kimsé; Dofara, Soro; Noel, Yapi Jean; Atcho, Otchoumou (European Scientific Journal, ESJ, 2017)
Determination of fibers level in grass-cutters (Thryonomys swinderianus, Temminck 1827) granulated diet: impacts on zootechnic performance. The grass-cutter or cane rat is a monogastric herbivore domesticated in Africa for meat production. Dietary fibre intake seems to play an important role in its digestive functioning, although the effects of fibre level on reproductive parameters of female cane rat remain largely unknown. An experiment was carried out to estimate the optimal fibre content of complete pelleted diets which optimizes the reproduction performance of female cane rat. Feed intake, digestible energy intake, and reproductive parameters of ad libitum fed female cane rat were studied for four diets differing in fibre levels (14, 18, 22 and 26 % of acid detergent fibre (ADF)) on 4 groups of 8 female animals. Each treatment was applied to an animal group. The increase in fibre content of the diet from 14 to 26 % ADF resulted in a decrease in the digestible energy (DE) content of the diet. However, feed intake increased (p ? 0.01) with increasing levels of fibre so that DE intake was not significantly different between treatments (245.05 kcal/kg DM on average). The animals’ average weight, average daily gain as well as the fecundity, prolificity, fertility, stillbirth and litter size have not been significantly impacted by dietary fibre level. The average values of these parameters were 3156 g ; 7.29 g/d; 47.11 % ; 52.32 % ; 90.18 % ; 7.71 % and 3.6 respectively. These results need to be confirmed in future experiments with higher numbers of animals.